Online newspapers use and homeland political participation potentials of the Nigerian students in Malaysia - Mustapha, Lambe Kayode; Saodah Wok, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2014)
The election time in any nation is a period for anxieties and expectations. It is also a period of heightened tripartite relationships between the candidates, the electorate and the media. While the citizens within the country rely mainly on the traditional media for information about election issues and candidates’ attributes, nations’ foreign residents bank on online versions of the homeland traditional media, particularly online newspapers. Although the impacts of traditional and new media on political participation within nations’ polity have received tremendous attention of scholars, little consideration has been accorded media use and political behaviour of foreign resident citizens whose transnational influence is becoming awesome in the contemporary time. Using cross-sectional survey design, this study samples Nigerian students in Malaysia higher learning institutions (N=312) with a view to examine the influence of online newspapers use on their political participation potentials in their homeland politics. Findings reveal weak but positive and significant correlations between online newspapers use and political interest on the one hand and online newspapers use and political participation on the other. The results thus show that reading online newspapers could be one of many factors cuing diasporic citizens to their homeland political development.